Incompatibilité du génitif et des constructions à tête adjectivale (*the disabled’s working conditions) – invariant sémantique et contrainte syntaxique sont-ils conciliables ? - Evelyne Chabert (Anglophonia)
NPs with adjectival heads (the rich, the French) cannot be used as modifiers in genitive constructions (*the disabled’s working conditions), but require the use of an of-phrase (the working conditions of the disabled). The aim of this paper is to try to account for this syntactic constraint by relating it to some semantic or pragmatic factor(s) that might explain why adjectival heads invariably trigger the selection of the of-phrase rather than that of the genitive.Such NPs are checked against three models (Henri Adamczewski’s, Ronald Flintham’s, and the author’s own), which are supposed to account for the factors at play in the choice between the genitive and the of-phrase. It appears however that none of these theories provides a satisfying explanation, since the construction in every case is shown to have all the properties required to be compatible with the genitive.The paper argues that the incompatibility is syntactic in essence and that it resides in the elliptic nature of adjectival heads. It also poses the question of the fallibility of semantic or pragmatic models, insofar as the invariant value that they put forward fails to relate the syntactic behaviour of each and every NP to some core semantic or pragmatic factor.